2020
DOI: 10.1038/s41598-020-79032-4
|View full text |Cite
|
Sign up to set email alerts
|

New discovery of two seismite horizons challenges the Ries–Steinheim double-impact theory

Abstract: The Nördlinger Ries and the Steinheim Basin are widely perceived as a Middle Miocene impact crater doublet. We discovered two independent earthquake-produced seismite horizons in North Alpine Foreland Basin deposits potentially related to both impacts. The older seismite horizon, demonstrated to be associated with the Ries impact, is overlain by distal impact ejecta in situ, forming a unique continental seismite-ejecta couplet within a distance of up to 180 km from the crater. The younger seismite unit, also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(47 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…1B). As seen elsewhere in the Molasse basin (Buchner et al 2020), clay-rich subsurface layers (aquitards) can locally increase the amount of fluids within overlying sands, thereby supporting the formation of soft-sediment seismites on an outcrop scale during an earthquake. The rare exposure of fossil sand diapirs near Winterthur may, therefore, indicate water saturation of the local substrate and its interaction with strong seismic waves.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…1B). As seen elsewhere in the Molasse basin (Buchner et al 2020), clay-rich subsurface layers (aquitards) can locally increase the amount of fluids within overlying sands, thereby supporting the formation of soft-sediment seismites on an outcrop scale during an earthquake. The rare exposure of fossil sand diapirs near Winterthur may, therefore, indicate water saturation of the local substrate and its interaction with strong seismic waves.…”
mentioning
confidence: 73%
“…The mid-Miocene Ries impact in southern Germany is Central Europe's biggest cosmic disaster in Phanerozoic geologic history. While earlier theories posited the Ries impact was contemporaneous with the smaller nearby Steinheim event in a double-impact scenario, it was recently shown that the Ries, with a Langhian age of 14.81 Ma (Schmieder et al 2018), predates Steinheim (Serravallian) by a few hundred thousand years (Buchner et al 2020). In addition to the distribution of impact ejecta, the Ries impact triggered a powerful (M W ~ 8.5) earthquake with far-reaching environmental effects (Buchner et al 2020).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The structure formed at 14.808 ± 0.038 Ma 17 . The nearby ~ 3.8 km in diameter Steinheim impact structure 19 is considered to have formed simultaneously, although this has been challenged in a recent publication 20 . The target bedrock is composed of sedimentary rocks of Triassic to Cenozoic age underlain by crystalline basement (Ref.…”
Section: Previous Work On the Blockhorizont And The Ries Impact Strumentioning
confidence: 99%